Vitamin D3 protects against glucocorticoid-induced muscle weakness and bone loss through a mechanism that requires VDR signaling only in skeletal muscle - Centeno, Viviana Andrea; Sato, AY.; Cregor, M.; Akel, NS.; Bellido, T. (2023)
Fil: Centeno, Viviana Andrea. Universidad Nacional de Córdoba. Facultad de Odontología. Cátedra Química Biológica A; Argentina.